THE INFLUENCE OF MURNAGHAN CONSTANTS ON THE PROPAGATION OF A TORSIONAL WAVE IN PRE-STRETCHED COMPOUND CIRCULAR CYLINDERS - Akbarov, S. D.; Ozturk, A. (SPRINGER, 2010)
The propagation of torsional waves in prestressed compound circular cylinders is investigated modeling them by a piecewise-homogeneous body and using the three-dimensional linearized theory of elastic waves in prestressed body. It is assumed that the elastic relations for the components of the cylinders include the Murnaghan potential. The numerical investigations are performed for bronze (Br) or brass (Pr) (for the solid cylinder) and steel (St) (for the hollow cylinder). The effect of the variation of the geometric (the ratio of the thickness of the outer cylinder to the radius of the inner cylinder) and mechanical parameters on the dispersion curves are analyzed using the numerical results obtained
Keywords: torsional wave; dispersion; initial stress; compound cylinder; Mechanics